From theory to practice - Farrell, Colleen (The Hastings Center report, 2012)
As I prepare to start medical school this fall and think back on my two years as a research assistant at The Hastings Center, I'm struck by how much I've learned and yet how much remains unknown to me. After two years of lunchtime conversations, project meetings, and debates in the research assistants' office, discussing issues ranging from reproduction to end-of-life care has become almost a way of life. At the same time, I'm reminded of a story my mom told me about her childhood piano teacher, Miss Belser, who told her that while she could certainly learn to play all the notes in the Moonlight Sonata, she was too young to know the heartache that makes the notes become music.